Functional block copolymers, heterogeneous catalysts and chain-end functionalized polymers in organocatalyzed living radical polymerization - Chang Jun Jie (Nanyang Technological University, 2020)
Reversible complexation mediated polymerization (RCMP) is an organocatalyzed living radical polymerization system. The motivation of this Ph.D. thesis is to further develop RCMP. The objectives include extending the applications of RCMP, increasing its ease of use, and improving its practicality to industry. In Chapter 1, the concept of radical polymerization is introduced and the principle as well as mechanisms of several living radical polymerization (LRP) systems will be discussed. The concept of block copolymers, macromonomers, heterogeneous catalysis and chain-end functionalized polymers along with examples of their applications are also mentioned. The motivations and aims of each chapter in this thesis will be discussed. In Chapter 2, a method of preparing block copolymers via RCMP was developed. A stable poly(methyl methacrylate) bearing a vinyl end-group (PMMA–Y) was employed as a macroinitiator precursor. PMMA–Y was transformed in situ into the active macroinitiator PMMA-iodide (PMMA–I) via addition-fragmentation chain transfer (AFCT), followed by RCMP with butyl acrylate (BA) to obtain block copolymers. Both the transformation and polymerization occur in one-pot and quantitative studies were conducted on the mechanism of transformation. The use of stable PMMA–Y overcomes the drawback of using isolated PMMA–I which lacks long-term stability, thereby making this block copolymerization method suitable for practical use due to its increased ease of operation. In Chapter 3, the scope of monomers was expanded for block copolymerization with PMMA–Y. AFCT of PMMA–Y generates the desired block copolymers, while propagation results in branched copolymers. Kinetic studies revealed the temperature dependence of AFCT and propagation of PMMA–Y in the styrene (St) polymerization, allowing efficient synthesis of PMMA–PSt block copolymers at higher temperatures, while branched copolymers were predominantly obtained at lower temperatures. AFCT of PMMA–Y was also found to be dominant at the temperatures used in the acrylonitrile and acrylate polymerizations, allowing for the respective block copolymers to be synthesized. The polymerization of BA using PMMA–Y with higher molecular weights was also performed, demonstrating the usefulness of this method for block copolymer synthesis. RCMP is typically performed using homogeneous catalysts such as tetrabutylammonium iodide (BNI). BNI was also the catalyst used in the block copolymerizations with PMMA–Y in Chapters 2 and 3, and one issue is the removal of such homogeneous catalysts after polymerization. In Chapter 4, polymer resin particles containing tertiary amine (R3N) and quaternary ammonium iodide (R4N+I−) functionalities were developed as supported catalysts for heterogeneous RCMP. The supported catalysts produced low dispersity homopolymers and block copolymers of several methacrylates and acrylonitrile. The catalysts were also easily recovered from the reaction mixtures and were recycled for 5 polymerizations without any significant decrease in their catalytic activity. The developed supported catalysts are attractive particularly for industrial applications of RCMP. Control over the polymer architecture was demonstrated in Chapter 3 through the selective synthesis of block copolymers and branched copolymers using high and low polymerization temperatures respectively. The next objective was the chain-end modification of polymer-iodides obtained from RCMP. In Chapter 5, the chain-end transformation of polyacrylate-iodides were carried out via an organocatalyzed radical addition to alkynes to obtain vinyl-iodide-terminated polymers. This transformation reaction was also amenable to functional alkynes bearing hydroxyl and trifluoromethyl functionalities. The chain-end transformations were comprehensively studied via matrix assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Such vinyl-iodide bearing polymers are potential precursors for cross-coupling reactions towards the development of functional polymer materials.